Inheritance Of Chick Weight And Egg Production In White Leghorn Birds - Rose Job T (Department of Animal Breeding and Genetics, College of Veterinary and Animal Sciences, 1983)
A research work was undertaken in two strains of White Leghorn birds to study the inheritance of chick weight and egg production. The birds maintained at the poultry farm under All India Co – ordinated Research Project on Poultry for Eggs, Mannuthy were utilized for the study. The mean values for six – week body weight (g), eight week body weight (g) and egg production upto 280 days of age (number) were 319.4 + 1.4, 452.9 + 1.8 and 71.5 + 0.4 for N strain and 351.2 + 1.7, 513.7 + 2.2 and 80.6 + 0.5 for P strains. Least squares analysis for effect of generations and hatches within generations were carried out. Generation effects were significant for the three characters in both the strains. Effect of hatches within generations were also found to be significant except for egg production in first generation batches and for six – week body weight in second generation hatches in N strain. The data were adjusted for the generation and hatch effects. Adjusted data were used to estimate heritability, genetic, phenotypic and environmental correlations. The heritability estimates in N strain were 0.223 + 0.112, 0.642 + 0.078 and 0.433 + 0.099 for six – week body weight 0.278 + 0.108, 0.372 + 0.068 and 0.325 + 0.095 for eight – week body weight and 0.219 + 0.095, 0.379 + 0.077 and 0.298 + 0.095 for egg production based on sire, dam and sire + dam components of variance respectively. The respective estimates in P strain were 0.405 + 0.110, 0.341 + 0.103 and 0.373 + 0.101 for six – week body weight, 0.354 + 0.110, 0.443 + 0.094 and 0.398 + 0.118 for eight – week body weight and 0.530 + 0.102, 0.230 + 0.130 and 0.380 + 0.131 for egg production. The genetic correlation estimates between six – week and eight – week body weight were found to be high and positive in both the strains. The phenotypic correlations were also found to be positive but lower compared to genetic correlation and similar in both the strains. The environmental correlations had also been positive though of still lesser magnitude in both the strains. In general, the correlation estimates between chick weights and egg production were found to be very low in both the strains. The results were not suggestive of any strong relationship between chick weights and egg production. Out of these three characters, only egg production deserved consideration in selection as chick weight in White Leghorns cannot be considered as an economic trait. It was estimated that an improvement of 7.57 eggs per generation could be expected in both the strains for standard deviations of 16.04 and 15.41 and heritabilities of 0.219 and 0.230 in N and P strains respectively, when selection of males is 8.5 per cent and females 16 per cent.